2018
DOI: 10.1002/tox.22547
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lead exposure enhances the sympathoexcitatory response associated with P2X4 receptor in rat stellate ganglia

Abstract: Chronic lead exposure causes peripheral sympathetic nerve stimulation, including increased blood pressure and heart rate. Purinergic receptors are involved in the sympathoexcitatory response induced by myocardial ischemia injury. However, whether P2X4 receptor participates in sympathoexcitatory response induced by chronic lead exposure and the possible mechanisms are still unknown. The aim of this study was to explore the change of the sympathoexcitatory response induced by chronic lead exposure via the P2X4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…A detailed description of the potential mechanism of neurotoxicity is beyond the scope of this study. Experimental studies in animals suggested as potential mechanisms: stimulation of the sympathetic preganglionic neurons,10 harm to the β-adrenergic system in the brain,11 downregulation of cardiac β1-adrenoceptor activity,14 upregulated expression of P2X4 receptor in satellite glial cells of the stellate ganglion,15 increased sensitivity of chemoreceptor reflex12 or decreased sensitivity of the baroreflex 13. To what extent these animal experiments can be translated to the human condition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the potential mechanism of neurotoxicity is beyond the scope of this study. Experimental studies in animals suggested as potential mechanisms: stimulation of the sympathetic preganglionic neurons,10 harm to the β-adrenergic system in the brain,11 downregulation of cardiac β1-adrenoceptor activity,14 upregulated expression of P2X4 receptor in satellite glial cells of the stellate ganglion,15 increased sensitivity of chemoreceptor reflex12 or decreased sensitivity of the baroreflex 13. To what extent these animal experiments can be translated to the human condition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…8 According to their pharmacological characteristics and chemical structure, P receptors can be divided into two categories: P1 receptors, which respond to adenosine, and P2 receptors which respond to ATP. P2 (nucleotide) receptors can be further divided into two subcategories: P2X receptors (P2X 1−7 ) and P2Y receptors (P2Y 1,2,4,6,11,12,13,14,15 ). 8,9 In peripheral ganglia, the P2X4 receptor is expressed in both satellite glial cells and neurons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8,9 In peripheral ganglia, the P2X4 receptor is expressed in both satellite glial cells and neurons. 10,11 Injury and stimulation cause the nerve endings to release ATP, thereby initiating an inflammatory response. In sympathetic ganglia, ATP can be released from both glial cells and neurons 12−14 and activate P2X4 to participate in the transmission of pathological signals.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GFAP was recently assessed to evaluate SGCs differentiation in cell culture condition [26].Collectively, GFAP was widely known as a marker of SGCs activation [27]. GS could catalyze adenosine triphosphate-dependent amidation of glutamate to glutamine and was known as a better marker for SGCs [28]. Tongtako et al found that SGCs in DRG were immunopositive for GFAP in dogs and monkeys, whereas GFAP in murine SGCs was absence.…”
Section: Introductionmentioning
confidence: 99%